Implementasi Program Rehabilitasi Sosial Dasar Bagi Penyandang Disabilitas di Kota Sukabumi - Putri, Laila Nur Redha; Amirulloh, M. Rijal; Meigawati, Dine (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the implementation of basic social rehabilitation programs for people with disabilities in Sukabumi City. The issues underlying this study are the uneven distribution of basic social rehabilitation services, limited human resources and budget, and suboptimal coordination among implementers. Sukabumi City has experienced fluctuations in the number of people with disabilities from 2020 to 2024, but only a small portion receive basic social rehabilitation services each year, indicating a disparity between needs and program reach. This study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. Informants in this study consisted of officials from the Sukabumi City Social Service and social pillars at the sub-district/village level. Data analysis in this study included data reduction, data presentation, and conclusion drawing. The theory used in this study was George C. Edward III's policy implementation model, which includes four variables: communication, resources, implementer disposition, and bureaucratic structure. The results of the study indicate that the implementation of the basic social rehabilitation program for persons with disabilities in Sukabumi City has shown positive progress, particularly in terms of inter-agency communication and implementer disposition. However, limitations in the resource dimension and the lack of optimal coordination at the technical level remain the main challenges that need to be addressed promptly. This underscores the importance of improving institutional capacity, strengthening the role of social pillars at the regional level, and increasing budget allocation to ensure the equity and sustainability of basic social rehabilitation services for people with disabilities.